1994
DOI: 10.1128/jb.176.17.5534-5536.1994
|View full text |Cite
|
Sign up to set email alerts
|

Coagulase expression in Staphylococcus aureus is positively and negatively modulated by an agr-dependent mechanism

Abstract: Expression of staphylocoagulase by agr+ Staphylococcus aureus depends on the growth phase, being maximal during exponential growth and decreasing sharply postexponentially, while an agr-deleted strain continuously expresses an intermediate level of coagulase. Therefore, coagulase expression appears to be both positively and negatively modulated by an agr-dependent mechanism.Staphylocoagulase is an extracellular protein produced by Staphylococcus aureus which promotes fibrin formation in human plasma by nonenzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
1
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 13 publications
3
37
1
2
Order By: Relevance
“…S1 in the supplemental material). As described previously, coa transcriptional activity was maximal during the exponential growth phase (35). Similarly, hla promoter activity was maximal during the stationary growth phase, as documented previously (8,18,19), demonstrating that both reporter constructs accurately reflected previously published studies of these promoters.…”
Section: Resultssupporting
confidence: 62%
“…S1 in the supplemental material). As described previously, coa transcriptional activity was maximal during the exponential growth phase (35). Similarly, hla promoter activity was maximal during the stationary growth phase, as documented previously (8,18,19), demonstrating that both reporter constructs accurately reflected previously published studies of these promoters.…”
Section: Resultssupporting
confidence: 62%
“…Analysis of twofold serial dilutions of total RNA from both strains revealed that the agr mutant produced at least 16 times as much fnb mRNA as the wild-type strain (data not shown). Unlike that of other negatively regulated genes (i.e., spa and coa) which are constitutively expressed in agr mutants (23,40), transcription of fnb was restricted to the first hour of growth (lag phase and first cell division).…”
Section: Resultsmentioning
confidence: 99%
“…The regulation of S. aureus-induced coagulation and fibrinolysis is a wellorchestrated series of events that should be beneficial for the bacterium. Timing is an essential aspect in these processes and it is worth noting that coagulase is produced during the early growth phase (Lebeau et al, 1994), whilst staphylokinase is produced in the late exponential phase of the S. aureus growth cycle (Bokarewa et al, 2006). It seems therefore plausible that the early release of coagulase will enable the bacteria to evade an innate immune response by promoting their uptake into the fibrin network, whilst staphylokinase released at a later time point will allow the bacteria to escape from the clot and cause systemic complications.…”
Section: Discussionmentioning
confidence: 99%